2010
DOI: 10.1097/jcn.0b013e3181ba2957
|View full text |Cite
|
Sign up to set email alerts
|

Motivating People to Learn Cardiopulmonary Resuscitation and Use of Automated External Defibrillators

Abstract: The purpose of this study was to test the effect of a motivational message on the intention of laypersons to learn cardiopulmonary resuscitation (CPR) and automated external defibrillator (AED) use. A pretest-posttest, double-blind, randomized design was used with 220 community-dwelling adults. Participants were randomly assigned to the treatment group reading the CPR and AED pamphlet emphasizing learning CPR and AED use to save someone they love and the 3-minute window for response time; or to the comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Thirteen surveys 20, 34, 36-43, 48-49, 93 , three qualitative studies 33,47,96 , one before-and-after study 45 and one RCT 46 reported on issues that relate to willingness to use public-access AEDs for OHCA.…”
Section: Willingness To Usementioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen surveys 20, 34, 36-43, 48-49, 93 , three qualitative studies 33,47,96 , one before-and-after study 45 and one RCT 46 reported on issues that relate to willingness to use public-access AEDs for OHCA.…”
Section: Willingness To Usementioning
confidence: 99%
“…McDonald et al 46 conducted an RCT where a control group received a leaflet encouraging CPR and AED use, and the intervention group received the same leaflet with two additional "motivational" messages about CPR and AEDs. Both groups were laypeople with no previous experience of CPR.…”
Section: Willingness To Usementioning
confidence: 99%
“…To our knowledge, no study using a brief intervention to raise awareness about CPR /first aid has been previously published. One study assessed the effectiveness of messages provided in pamphlet form, in increasing the general population's motivation to learn CPR but it did not involve GPs (McDonald et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…One study assessed the effectiveness of messages provided in pamphlet form, in increasing the general population’s motivation to learn CPR but it did not involve GPs (McDonald et al. , 2010 ).…”
Section: Introductionmentioning
confidence: 99%